Spatial Patterns and Determinants of the Human Development Index: An Esda Approach - Aprelia, Nata Widya; Nurman Setiawan Fadjar (Journal of Development Economic and Social Studies, 2026)
Inequalities in human development in East Java are reflected in a 22.75 point range in the Human Development Index (HDI) across districts and cities, forming a cluster pattern. This study aims to identify the spatial patterns of the HDI and its determining factors using a quantitative panel data approach covering 38 districts and cities for the period 2019–2024. The analysis was conducted using ESDA and panel data regression. ESDA results indicate significant spatial clusters with a hotspot in Gresik and coldspots in Pamekasan and Sampang. However, the panel Lagrange Multiplier test demonstrated no spatial dependence after controlling for independent variables, leading to the selection of CEM as the best model. The primary determinants of the HDI are Average Years of Schooling, Expected Years of Schooling, Life Expectancy, and Real Per Capita Expenditure, all of which have a significant positive influence. These findings confirm Human Capital Theory while rejecting the hypothesis of structural spatial dependence. The implication is that human development policies need to prioritize improving the internal quality of regions, particularly in education and health, rather than relying on spatial spillover effects.